Acceptance and commitment therapy for high frequency episodic migraine without aura: Findings from a randomized pilot investigation. Issue 6 (11th June 2021) - Grazzi, Licia; Andrasik, Frank; Rizzoli, Paul; Bernstein, Carolyn; Sansone, Emanuela; Raggi, Alberto
Abstract: Objective: We compared the incremental effects of adding acceptance and commitment therapy (ACT) to pharmacological treatment as usual (TAU) in a sample of patients with high frequency episodic migraine without aura (HFEM), assessing impact on a spectrum of measures across multiple domains. Background: Patients with HFEM are at risk of developing chronic migraine and medication overuse headache. ACT has been shown to be effective for the treatment of various chronic pain conditions, but little attention has been given to its therapeutic value in the management of recurring headaches. Methods: In this single‐blind (masking for outcome assessor), open‐label, randomized clinical trial, 35 patients with HFEM, with a monthly headache frequency ranging from 9 to 14 days, were recruited at the headache center of C. Besta Neurological Institute and randomized to either TAU (patient education and pharmacological prophylaxis; n  = 17) or TAU + ACT ( n  = 18). Patients assigned to the combined treatment arm additionally received six 90‐min weekly group sessions of ACT therapy and two supplementary "booster" sessions. All patients were on a stable course of prophylactic medication in the 3 months prior to initiating either treatment. Monthly headache frequency served as the primary outcome measure, with all other data collected being considered as secondary measures (medication intake, disability, headache impact, anxiety and depression, catastrophizing, allodynia, cognitive inflexibility, pain acceptance, mindful attention and awareness). Results: A total of 35 patients were enrolled: 17 randomized to TAU, of whom three dropped out, and 18 to TAU + ACT (no dropouts in this group). Headache frequency and medication intake decreased in both groups over 12 months, with patients in the TAU + ACT group showing statistically significant reduction earlier, that is, by month 3. Headache frequency was reduced by 3.3 days (95% CI: 1.4 to 5.2) among those randomized to ACT + TAU, whereas it increased by 0.7 days (95% CI: −2.7 to 1.3) among those randomized to TAU only ( p  = 0.007, partial η 2  = 0.21), the difference being 4 days (95% CI: 1.2 to 6.8). Medication intake was reduced by 4.1 intakes (95% CI: 2.0 to 6.3) among those randomized to ACT + TAU and by 0.4 intakes (95% CI: −1.8 to 2.5) among those randomized to TAU only ( p  = 0.016; partial η 2  = 0.17), the difference being 3.8 intakes (95% CI: 0.7 to 6.8). At 6 and 12 months, the variations were not different between the two groups for headache frequency and medication intake. The opposite was found for measures of headache impact and pain acceptance, where the differences over time favored patients allocated to TAU. Both groups improved with regard to measures of disability, anxiety and depression, catastrophizing, and cognitive inflexibility, whereas measures of allodynia and pain acceptance were stable over time. Conclusions: Our preliminary findings indicate that supplementing TAU with ACT can enhance the main clinical outcomes, namely headache frequency and medication intake of patients with HFEM.